Grease quality issues on middle voltage switchgear: corrosivity resistivity safety and ageing. - Mohd Sabri, Mahmud; Sanuri, Ishak; Mohd Najib, Razali; Mohd Aizudin, Abdul Aziz; Musfafikri, Musa (IIUM, Malaysia, 2019)
Grease products recommended by OEM for conventional 11kV switchgears are generally trusted. Some disadvantages might however exist among them or their supply could be insufficient and lead to use of non-OEM-recommended grease. This paper reports analysis methods to evaluate both types of grease that were recently used in the switchgears at local electrical distribution stations owned by Tenaga Nasional Berhad. Hardened, greenish and severely irritating greases probably caused by incompatible compounding, electrochemical reaction, and hazardous components, respectively, were among common problems faced by workers. Eight physical tests and four chemical tests were conducted on 10 grease samples using thermogravimetry, switchgear rig, gas chromatography and infrared spectroscopy besides other equipment and standard methods. Grease stability, oil bleeding, flammability of grease droplet and dropping point were among the characteristics determined in the analyses. The results reveal copper corrosion, chemical change, instable and inconsistent grease, and toxics in grease, which surprisingly included the OEM-recommended one.